Targeting the B-cell receptor pathway in diffuse large B-cell lymphoma. (April 2018) - Dunleavy, Kieron; Erdmann, Tabea; Lenz, Georg
Highlights: The B-cell receptor pathway is a critical signaling cascade in diffuse large B-cell lymphoma (DLBCL). Advances in elucidating various components of it and critical enzymatic steps in its activation have led to the development of many inhibitors of BCR signaling. These inhibitors are now being tested in DLBCL and have shown interesting activity in systemic DLBCL and a subtype of DLBCL called primary CNS lymphoma (PCNSL). There is much interest in identifying the role of this class of agents in the management of systemic DLBCL and PCNSL. Abstract: Diffuse large B-cell lymphoma (DLBCL) is a heterogeneous diagnostic category with different molecular subtypes defined by distinct gene expression patterns and divergent mechanisms of oncogenic activation. Several studies have suggested an inferior survival for patients of the activated B-cell-like (ABC) versus the germinal center B-cell-like (GCB) DLBCL subtype which has led to increasing interest in investigating pharmacological inhibition of signaling pathways which contribute to lymphomagenesis and that are specifically utilized by ABC DLBCL cells. One of these signaling cascades is the B-cell receptor (BCR) pathway and several approaches in clinical trials to target this cascade have demonstrated promising therapeutic activity. This review discusses our current understanding of the role of BCR signaling in different DLBCL subtypes, including primary central nervous system lymphoma (PCNSL), a subgroup of DLBCL that is particularly dependent on BCR signaling. One specific aim of this review is to highlight novel approaches to therapeutically target BCR signaling in DLBCL.